When words hurt ... literally. A case report of temporomandibular joint dislocation in a patient with Tourette's syndrome - Jaromir Kargol; Tomasz Krzysztof Bąk; Jolanta Wojciechowicz; Anna Gawęda; Tomasz Tomaszewski (Kazimierz Wielki University, 2018)
Tourette's syndrome is a disease from the borderlands of psychiatry and neurology. Its course consists of chronic motor tics, vocal tics or vocalizations. The first symptoms appear in childhood or adolescence. Tics may cause body injuries. In this case, tics probably have contributed dislocation of the temporomandibular joints.